Hawaiian and Strombolian style monogenetic volcanism in the extra-Andean domain of central-west Argentina - Bertotto, Gustavo Walter (2006)
In the provinces of Mendoza and La Pampa (central-western Argentina), retroarc volcanism was active from the Miocene through historic times. There are approximately 40 basaltic eruptive centers between 36°S and 37°30′S to the East of 68°40′W. These centers were studied in order to define their volcanological evolution. The vents are constituted of seven lithofacies: i.e., (A-1) weakly welded lapilli and bomb beds; (A-2) agglutinated spatter and bomb beds; (A-3) agglutinated spatter beds; (B) ash beds; (C) lava flows; (D) conduit fill; and (E) dikes. Three eruptive episodes (phases) were identified. The first one generated agglutinated spatter and bomb beds (lithofacies A-2), which constitute the internal part of the edifices. These are followed by weakly welded lapilli and bomb beds (lithofacies A-1) and agglutinated spatter beds (lithofacies A-3). The final episode includes lava flows (lithofacies C), minor agglutinated spatter deposits (lithofacies A-3) and isolated lapilli and bomb clasts. We postulate Hawaiian style fountaining activity as responsible for the generation of agglutinated spatter and bombs beds, and variations between Strombolian and Hawaiian activity for the formation of successions of weakly welded lapilli and bomb beds and agglutinated spatter beds. The vent features and the homogeneity of the erupted magma suggest that the studied volcanoes were monogenetic. © 2006 Elsevier B.V. All rights reserved.